EFEKTIFITAS KOMUNIKASI PEMASARAN HUMAS TERHADAP PEMILIHAN PENDIDIKAN - Jahid Syaifullah (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
The growth of private universities has made the competition process for new students to be tighter. Private universities must make efforts to increase the interest of prospective new students to choose to continue their education at these private universities. In addition to efforts to improve the quality of education services,This research is quantitative descriptive. The study population was all members of the Karanganyar scout movement branch quartir, while the research sample was 50 students. Data collection used a questionnaire, while data analysis used univariate and bivariate analysis.The results showed that most of the respondents stated that the marketing communication of the Indonusa Polytechnic was quite good (66%), most of the respondents stated that their interest in studying at the Indonusa Polytechnic was moderate (58%), and there was a significant relationship between marketing communication and interest in studying for new students. Indonusa Surakata Polytechnic. The conclusion of this research is that there is a relationship between marketing communication and interest in studying at Polytechnic Indonusa Surakarta.